(untitled) (Research, Society and Development, 2021)
Objective: To present scientific evidence based on a systematic literature review (PRISMA) on the interference of the lingual frenulum in the functions of the oral motor sensory system in children. Methodology: The search for articles was carried out in the Scielo, Lilacs, Pubmed, Scopus, Bireme and Web Of Science databases, there was no restriction on location, period and language. The descriptors were selected from the Health Sciences Descriptors (DeCS) and Medical Subject Heading Terms (MeSH) dictionary. In addition, a search for gray literature was carried out on Google Scholar. Results: Initially, 131 articles were selected in all the cited search bases, scaled to 121 after exclusion by repetition; then, the titles and abstracts were analyzed and 119 papers were excluded because they did not adhere to the proposed study, therefore two articles were admitted for the final and total analysis. Conclusion: Research that addresses the interference of the lingual frenulum in oral functions, mostly, is related to sucking and breastfeeding, but they are still in small numbers.